Elucidating the interfacial evolution and anisotropic dynamics on silicon anodes in lithium-ion batteries. (July 2019) - Shi, Yang; Wan, Jing; Li, Jin-Yi; Hu, Xin-Cheng; Lang, Shuang-Yan; Shen, Zhen-Zhen; Li, Ge; Yan, Hui-Juan; Jiang, Ke-Cheng; Guo, Yu-Guo; Wen, Rui; Wan, Li-Jun
Abstract: Silicon (Si) has been considered as one of the most promising anodes in secondary high-energy rechargeable lithium-ion batteries (LIBs) owing to its high theoretical specific capacity and abundant reserves, whereas it suffers from an unstable solid electrolyte interphase (SEI) film and dramatic volume expansion. Herein, in situ electrochemical atomic force microscopy (AFM) and visual videos were used to reveal the interphasial properties of SEI film and anisotropic dynamics upon lithiation/delithiation processes on the single-crystalline Si electrodes with different crystal plane orientations. Lithiation of Si (111) prefer to grow along the <121> direction in the XY plane with the shape of oriented rods, in contrast, that of Si (100) form cone-like structure with the axial direction of <100> perpendicular to the (100) surface. Quantitative dynamic processes elucidate the preferable reversibility in Si (111) system, revealing the corresponding structure-reactivity correlations. Graphical abstract: Anisotropic dynamics upon LiSi alloying/dealloying reactions on the single crystalline Si anodes with different crystal plane orientations were revealed by in situ AFM. Lithiation of Si (111) occur along the <121> direction with the shape of oriented rods in the XY plane, whereas that of Si (100) form cone-like structure with the axial direction of <100> perpendicular to the (100) surface. Image 1 Highlights: Lithiation/delithiation processes on Si anodes are in situ monitored using electrochemical AFM. Interfacial evolution and dynamics greatly vary with Si (111) and Si (100) electrodes. Lithiation of Si (100) tends to proceed along the axial direction of <100> with severe volume expansion induce poor reversibility. Oriented growth along the <121> direction in the XY plane during lithiation of Si (111) with less volume change.